Health beliefs and engagement in moderate-to-vigorous intensity physical activity among cancer survivors: a cross-sectional study - Price, Jenson; Barrett-Bernstein, Meagan; Wurz, Amanda; Karvinen, Kristina; Brunet, Jennifer (Université d'Ottawa | University of Ottawa, 2020)
Purpose: Moderate-to-vigorous-intensity physical activity (PA) can alleviate many adverse side effects and symptoms caused by cancer treatments; yet, most cancer survivors are insufficiently active. Evidence shows that theory-based PA behavior change interventions are more effective than non-theory-based interventions; thus, it is necessary to ascertain modifiable theoretical factors associated with moderate-to-vigorous-intensity PA among cancer survivors. Drawing on the health belief model (HBM), the associations between moderate-to-vigorous-intensity PA and (1) perceived susceptibility to cancer recurrence and health problems, (2) perceived severity of cancer recurrence and health problems, (3) perceived benefits of PA for reducing risk of cancer recurrence and health problems, (4) perceived barriers to PA, and (5) PA barrier self-efficacy among cancer survivors were examined. Methods: A total of 123 adult cancer survivors (Mage = 50.1 ± 15.5 years; 82.9% female) completed an online self-report survey assessing sociodemographic and medical characteristics, moderate-to-vigorous-intensity PA, and the HBM constructs. Data were analyzed descriptively and using hierarchical linear regression analysis. Results: After adjusting for age, sex, body mass index, time since cancer diagnosis, and treatments received, the HBM constructs collectively explained 29% of the variance in moderate-to-vigorous-intensity PA. Perceived benefits of PA (β = .20, 95% CI [1.81, 11.67], p = .007) and PA barrier self-efficacy (β = .42, 95% CI [0.26, 0.53], p < .001) were significantly associated with moderate-to-vigorous-intensity PA. Conclusion: Raising awareness of the benefits of PA for reducing risk of cancer recurrence and health problems and strengthening self-efficacy to overcome PA barriers may help to promote cancer survivors’ attainment of moderate-to-vigorous-intensity PA guidelines.
This version of the article has been accepted for publication, after peer review (when applicable) and is subject to Springer Nature’s AM terms of use, but is not the Version of Record and does not reflect post-acceptance improvements, or any corrections. The Version of Record is available online at: http://dx.doi.org/10.1007/s00520-020-05515-9
Keywords: Oncology; Theory; Adults; Self-efficacy; Health behavior; Survivorship